2018
DOI: 10.1007/s11051-018-4397-x
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring nanoparticles in the size range to 2000 nm

Abstract: Measurement of light scattered from suspensions of monodisperse nanoparticles in solution (“turbidity”) long has been used to derive their size. Following some means of fractionation, the light (monochromatic) scattered by the particles into a set of distinct angles is collected and a non-linear least squares fit was made to an appropriate theory in order to extract their size. For a wide range of particle structures, where this process becomes very complex and of questionable validity, there is a far simpler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A number of extrapolation methods are provided by commercial software, some based only on the theory of light scattering, others based on further assumptions on the geometry of the particles. The choice of the correct extrapolation method is not always straightforward and may lead to substantial estimation errors [ 82 ]. A systematic study of the applicability of each method can be found in Andersson et al [ 83 ].…”
Section: Determine Size Distribution and Physical Properties Of Nanocmentioning
confidence: 99%
“…A number of extrapolation methods are provided by commercial software, some based only on the theory of light scattering, others based on further assumptions on the geometry of the particles. The choice of the correct extrapolation method is not always straightforward and may lead to substantial estimation errors [ 82 ]. A systematic study of the applicability of each method can be found in Andersson et al [ 83 ].…”
Section: Determine Size Distribution and Physical Properties Of Nanocmentioning
confidence: 99%
“…An analysis of conformation plots according to molecular mass and root mean square (RMS) radius could give more structure information of polysaccharides [ 17 ]. The distributions of molar mass and rms radius are shown in Figure 3 a,b respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For data analysis, the refractive index increment (dn/dc) was adjusted to 0.1721 mL/g for sense and antisense AluSx1 RNA samples ( 35–37 ). Data were analysed using the ASTRA v9 software package (Wyatt Technology, USA) ( 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%